The Role of Birds as Bioindicators in Assessing Environmental Quality - Husaeri, Husaeri (Maliki Interdisciplinary Journal, 2024)
Ecosystems are reciprocal interactions between biotic and abiotic components that form biodiversity. Bioindicators, such as birds, can be used to measure environmental quality due to their sensitivity to habitat changes. Birds, which belong to the vertebrate group, have important roles in the ecosystem, such as dispersal of seeds and controlling insect populations. The existence of birds also reflects environmental health, which is relevant to the concept in Surah Al-Mulk verse 19 regarding the creation of birds by Allah with a special role. This paper aims to examine the potential of birds as bioindicators of environmental quality, including their characteristics, advantages, disadvantages, as well as challenges and opportunities in environmental conservation.